Photoreceptors Diversity of Fishes Eyes: (A Review) - Abdul Razak (International Journal of Ecophysiology, 2019)
This article is a review about the diversity of photoreceptors in various fishes. In this article, the author discusses the photoreceptors of freshwater fish, reef fish, sharks and tuna, and deep sea fish. The purpose of this article are to provides illustration and explanations about the diversity of photoreceptor of fish eye and its relationship with the ecosystem. The information is important in the development of fishery technology.